Isolation, identification, recombination analysis and pathogenicity experiment of a PRRSV recombinant strain in Sichuan Province, China - Tu, Teng; Li, Yanwei; Zhang, Guidong; Du, Chengchao; Zhou, You; Jiang, Dike; Luo, Yan; Yao, Xueping; Yang, Zexiao; Ren, Meishen; Wang, Yin (Frontiers in Microbiology, 2024)
Since 2013, the porcine reproductive and respiratory syndrome virus type 2 (PRRSV-2), lineage 1.8 (NADC30-like PRRSV) has emerged and become widely prevalent in China. The NADC30-like PRRSV poses significant challenges for disease control, primarily because of its propensity for frequent mutations and recombinations. We successfully isolated and identified a NADC30-like strain, designated SCCD22, in Chengdu, Sichuan Province, China. We meticulously examined the genetic recombination properties and evaluated its pathogenicity in 28-day-old piglets. SCCD22 showed 93.02% nucleotide homology with the NADC30 PRRSV strain, and its nonstructural protein 2 coding region showed the same 131 amino acid deletion pattern as that seen in NADC30. Furthermore, we identified two recombination events in SCCD22: one in the NSP2 region (1028-3290 nt), where it was highly similar to the JXA1-like strain GZ106; and another in the NSP10~12 region (9985-12279 nt), closely resembling the NADC30-like strain CY2-1604.Piglets infected with SCCD22 exhibited clinical symptoms such as elevated body temperature, prolonged fever, reduced appetite, and roughened fur. Postmortem examinations underscored the typical lung pathology associated with PRRSV, indicating that the lungs were the primary affected organs. Furthermore, extended viral shedding accompanied by progressive viremia was observed in the serum and nasal excretions of infected piglets. In summary, this study reports a domestic PRRSV recombination strain in the Sichuan Province that can provide critical insights into preventing and controlling PRRSV in this region.